Demethylating therapy increases cytotoxicity of CD44v6 CAR-T cells against acute myeloid leukemia - Tang, Ling; Kong, Yingjie; Wang, Haobing; Zou, Ping; Sun, Ting; Liu, Ying; Zhang, Juan; Jin, Na; Mao, Hanwen; Zhu, Xiaojian; Wang, Jue; Meng, Fankai; et al. (Frontiers in Immunology, 2023)
CD44v6 chimeric antigen receptor T (CD44v6 CAR-T) cells demonstrate potent anti-tumor ability and safety in acute myeloid leukemia (AML). However, the application of CD44v6 CAR-T is adversely affected by transient fratricide and exhaustion of CD44v6 CAR-T cells due to CD44v6 expression on T cells. The exhaustion and functions of T cells and CD44v6 expression of AML cells are associated with DNA methylation. Hypomethylating agents (HAMs) decitabine (Dec) or azacitidine (Aza) have been widely used to treat AML. Therefore, CD44v6 CAR-T cells and HAMs may have synergy against AML. CD44v6 CAR T cells or AML cells were pretreated with Dec or Aza, and the cytotoxicity of CD44v6 CAR-T cells to AML was detected. Our results revealed that Dec and Aza improved the functions of CD44v6 CAR-T cells through increasing the absolute output of CAR+ cells and persistence, promoting activation and memory phenotype of CD44v6 CAR-T cells, and Dec had a more pronounced effect. Dec and Aza promoted the apoptosis of AML cells, particularly with DNA methyltransferase 3A (DNMT3A) mutation. Dec and Aza also enhanced the CD44v6 CAR-T response to AML by upregulating CD44v6 expression of AML cells regardless of FMS-like tyrosine kinase 3 (FLT3) or DNMT3A mutations. The combination of Dec or Aza pretreated CD44v6 CAR-T with pretreated AML cells demonstrated the most potent anti-tumor ability against AML. These findings demonstrate that Dec or Aza combined with CD44v6 CAR-T is a promising therapy for AML.